The False Promise of Quantum Mechanics - Sansbury, Timothy (Zygon, 2007)
Abstract. The causal indeterminacy suggested by quantum mechanics has led to its being the centerpiece of several proposals for divine action that does not contradict natural laws. However, even if the theoretical concerns about the reality of causal indeterminacy are ignored, quantum-level divine action fails to resolve the problem of ongoing, responsive divine activity. This is because most quantum-level actions require a significant period of time in order to reach macroscopic levels whether via chaotic amplification or complete divine control of quantum events. Therefore, quantum-level divine action either requires divine foreknowledge of purportedly free or random events or imposes such limitations on divine actions that they become late, potentially impotent, and confused. I argue that the theological problem of divine action remains; even at its most promising, quantum mechanics offers insufficient resolution. This failure suggests a reexamination of the assumptions that God is temporal and lacks foreknowledge of future contingencies.